KEPEMIMPINAN ISLAMI DALAM PENINGKATAN MUTU LEMBAGA PENDIDIKAN ISLAM - Subhan, Moh. (e-Journal STAI Muhammadiyah Tulungagung, 2013)
Development of quality Islamic education institutions one of which will be greatly influenced by the leadership that was developed by individuals who have been given the task of leading Islamic educational institution. Islamic leadership has several characteristics that can be used leader Isam educational institutions in performing the task of leadership. Islamic leadership is the concept of the balance between worldly leadership and the concept of hereafter, to reach the ultimate goal of the organization is more than just a temporary purpose, demands a high commitment to the principles of Islam and put the task of leadership is not just a humanitarian tasks that are not accounted for in addition to the member, but will be held accountable before God Almighty as well.